COMBATING DOMESTIC VIOLENCE: The Maria da Penha Law, the implementation of public policies and an analysis of the Escuta Ativa Institute (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The aim of the article is to analyze the concept of public policy, its formulation, application and monitoring in the context of domestic violence, based on the Maria da Penha Law (Law No. 11.340/2006). Through a bibliographical review and analysis of the Law, the paper addresses its relevance as a mechanism for protecting women's rights, internationally recognized for incorporating a gender perspective into the political and legal spheres. In the first chapter, the article contextualizes the Maria da Penha Law in relation to international treaties on women's rights, highlighting its importance in both the legal and practical spheres. The second chapter discusses the concept of public policy according to the Law and academic literature, especially the works of Wânia Pasinato and Fabiana Severi, which deal with domestic violence and the efficiency of public policies in this area. The final chapter analyzes the Instituto Escuta Ativa project, showing that it does not meet the public policy criteria established by the Maria da Penha Law, compromising its effectiveness in combating violence against women.